dRYBP counteracts chromatin-dependent activation and repression of transcription. - Sol Fereres; Rocío Simón; Adone Mohd-Sarip; C Peter Verrijzer; Ana Busturia (PLoS ONE, 2014)
Chromatin dependent activation and repression of transcription is regulated by the histone modifying enzymatic activities of the trithorax (trxG) and Polycomb (PcG) proteins. To investigate the mechanisms underlying their mutual antagonistic activities we analyzed the function of Drosophila dRYBP, a conserved PcG- and trxG-associated protein. We show that dRYBP is itself ubiquitylated and binds ubiquitylated proteins. Additionally we show that dRYBP maintains H2A monoubiquitylation, H3K4 monomethylation and H3K36 dimethylation levels and does not affect H3K27 trimethylation levels. Further we show that dRYBP interacts with the repressive SCE and dKDM2 proteins as well as the activating dBRE1 protein. Analysis of homeotic phenotypes and post-translationally modified histones levels show that dRYBP antagonizes dKDM2 and dBRE1 functions by respectively preventing H3K36me2 demethylation and H2B monoubiquitylation. Interestingly, our results show that inactivation of dBRE1 produces trithorax-like related homeotic transformations, suggesting that dBRE1 functions in the regulation of homeotic genes expression. Our findings indicate that dRYBP regulates morphogenesis by counteracting transcriptional repression and activation. Thus, they suggest that dRYBP may participate in the epigenetic plasticity important during normal and pathological development.